Guiding Principles for Designing Highly Efficient Metal‐Free Carbon Catalysts. Issue 13 (7th December 2018) - Zhang, Lipeng; Lin, Chun‐Yu; Zhang, Detao; Gong, Lele; Zhu, Yonghao; Zhao, Zhenghang; Xu, Quan; Li, Hejun; Xia, Zhenhai
Abstract: Carbon nanomaterials are promising metal‐free catalysts for energy conversion and storage, but the catalysts are usually developed via traditional trial‐and‐error methods. To rationally design and accelerate the search for the highly efficient catalysts, it is necessary to establish design principles for the carbon‐based catalysts. Here, theoretical analysis and material design of metal‐free carbon nanomaterials as efficient photo‐/electrocatalysts to facilitate the critical chemical reactions in clean and sustainable energy technologies are reviewed. These reactions include the oxygen reduction reaction in fuel cells, the oxygen evolution reaction in metal–air batteries, the iodine reduction reaction in dye‐sensitized solar cells, the hydrogen evolution reaction in water splitting, and the carbon dioxide reduction in artificial photosynthesis. Basic catalytic principles, computationally guided design approaches and intrinsic descriptors, catalytic material design strategies, and future directions are discussed for the rational design and synthesis of highly efficient carbon‐based catalysts for clean energy technologies. Abstract : The theoretical analysis and material design of metal‐free carbon nanomaterials as efficient photo‐/electrocatalysts to facilitate critical chemical reactions in clean energy technologies are considered. Basic catalytic principles, computationally guided design approaches and descriptors, material design strategies, and future directions are discussed for the rational design and synthesis of highly efficient catalysts for clean energy conversion and storage.